Предмет: Алгебра,
автор: kravczova2000
СРОЧНО!!!!Даю 35 баллов!!!!
Приложения:
Ответы
Автор ответа:
0
(х-6)^2-х(х+8)=2
(х^2-12х+36)-(х^2+8х)=2
х^2-12х+36-х^2-8х=2
-12х+36-8х=2
-20х=2-36
-20х=-34
х=17/10
или 1,7
(х^2-12х+36)-(х^2+8х)=2
х^2-12х+36-х^2-8х=2
-12х+36-8х=2
-20х=2-36
-20х=-34
х=17/10
или 1,7
Похожие вопросы
Предмет: Литература,
автор: georgy90
Предмет: Музыка,
автор: pomidorunu
Предмет: Геометрия,
автор: lizakarashkina
Предмет: Биология,
автор: ни1234
Предмет: Литература,
автор: кучум2004